Jenis style shifting tokoh Conan Edogawa dalam film Meitantei Conan: Tengoku no countdown: Kajian sosiolinguistik - Jessen Alexander Christian; Umul Khasanah (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
Speech style changes are often employed by characters in films to adapt to communicative situations, interlocutors, and the identities they intend to present. This study aims to describe the types of style shifting used by the character Conan Edogawa in the film Detective Conan: Countdown to Heaven (Meitantei Conan: Tengoku no Countdown). This study employs a sociolinguistic approach using a qualitative descriptive method and content analysis. The data consist of Conan Edogawa’s utterances that demonstrate instances of style shifting in the film. The data were collected through observation, identification, transcription, classification, and analysis based on the theories of William Labov (1972), M. A. K. Halliday (1978), and John J. Gumperz (1982). The findings reveal three types of style shifting: role-based shifting, situational shifting, and internal–external shifting. The most dominant types are role-based shifting and internal–external shifting, each occurring in four data, while situational shifting appears in two data. The findings indicate that Conan’s speech style changes are primarily influenced by the social roles he performs and the shift between his true identity as Kudo Shinichi and his disguised identity as Edogawa Conan.